Analysis of Telecommunications Network Quality and Public Service Delivery in Busang Sub-District Using NVivo - Alda Ramadani; Muhammad Satya Satria (Journal of Social Research, 2026)
This research analyzes interview data from five informants in Busang Sub-District, Kutai Timur Regency, East Kalimantan, Indonesia, to examine the impact of telecommunications network quality on public service delivery. Using a qualitative descriptive approach, the research reveals that weak and unstable mobile and internet signals, particularly in remote villages, significantly hinder administrative services such as document processing, online registrations, and information access. Key challenges include frequent signal dropouts, delayed online transactions, and reliance on manual processes, exacerbated by Busang's status as a blank spot area. Findings indicate that poor network coverage reduces service reliability, responsiveness, and accessibility, aligning with prior studies on rural digital divides. The research contributes to policy discussions on digital inclusion in underdeveloped regions by providing micro-level qualitative insights often absent from aggregate reports. Recommendations include targeted infrastructure investments such as topography-specific micro-BTS deployments, hybrid offline-online service models to maintain accessibility during network failures, and community-based connectivity solutions to enhance public service equity in remote areas.